INFLUENCE TIME AND TEMPERATUR CONFUCION FRESH SEMEN PERANAKAN ETTAWA (PE) GOAT - Rikhardus En Juma (Jurnal Sains Peternakan, 2014)
Problems is formulation interior thorough this be how influence time and temperature preserving fresh cement Peranakan Etawa (PE) Goat about motility spermatozoa. Where as purpose thorough this for now influence time and temperature preserving fresh cement Peranakan Etawa (PE) Goat about motility spermatozoa. Hypothesis interior through this be contained influence time and temperature preserving fresh cement Peranakan Etawa (PE) Goat about motility spermatozoa. See through the will be fresh cement Peranakan Etawa Goat from animal husbandry Mr Dono in a place in Blitar. The research method used was Completely Randomized Design (CRD) Factorial. Research used was fresh cement Peranakan Ettawa goat. The result of the research indicated that spermatozoa quality of Peranakan Etawwa goat at 5°C in different preserving time within and without extender showed the significant differency (P<0, 01). However contained influence the very obvious time confusion fresh cement peranakan Etawa goat about temperature confusion nor such interaction the two of them. Conclusion the hardearned from product through this that is storage from temperature at 5°C see quality the most good that is capable hold out to long confusion in 45 hours as compared with storage from temperature space the only capable hold out to long confusion in 30 hours.Keywords: Time and temperature various, fresh semen, Peranakan Etawa goat, motility Spermatozoa